1st case [compact disc, unabridged] - Patterson, James, 1947-; Tebbetts, Christopher (Hachette Book Group, 2020)
Angela Hoot's hacking skills get her kicked out of MIT and into the Bureau's cyber-forensics unit. As Angela races to crack a killer's digital code, their rivalry escalates.